Fraudulent click detection - Kang, Eileen Mun Yee. (2013)
Online advertising has been popular with the emergence of Internet and the pay-per-click advertising model was one of the popular advertising models, however it poses problems to advertisers because of fraudulent clicks. It is a difficult and time-consuming task to identify fraudulent clicks manually. In this project, we try to solve this problem by using machine learning techniques.